Neurobehavioral Consequences of Traffic-Related Air Pollution - Salvi, Ankita; Salim, Samina (Frontiers in Neuroscience, 2019)
Traffic-related air pollution (TRAP) is a major contributor to global air pollution. The World Health Organization (WHO) has reported that air pollution due to gasoline and diesel emissions from internal combustion engines of automobiles, trucks, locomotives and ships leads to 800,000 premature deaths annually from pulmonary, cardiovascular and neurological complications. It has been observed that individuals living and working in areas of heavy vehicle traffic have high susceptibility to anxiety, depression and cognitive deficits. Information regarding the mechanisms that potentially lead to detrimental mental health effects of TRAP is gradually increasing. Several studies have suggested that TRAP is associated with adverse effects in the central nervous system (CNS), primarily due to increase in oxidative stress and neuroinflammation. Animal studies have provided further useful insights on the deleterious effects of vehicle exhaust emissions (VEE). Mechanistic basis for these effects is unclear, although gasoline and diesel exhaust-induced neurotoxicity seems the most plausible cause. Several important points emerge from these studies, first, TRAP leads to neurotoxicity. Second, TRAP alters neurobehavioral function. Exactly how that happens remains unclear. This review article will discuss current state of the literature on this subject and potential leads that have surfaced from the pre-clinical work.